Football in the chain of fan violence – from media perspective - Milenković, Vesna; Milenković, Dejan (Sociološki pregled, 2022)
The aim of the conducted research is the perception of football in a chain of fan violence, with a special overview of the reporting of the media as social subjects whose task is to encourage other agents of the society to understand more seriously the problem and to respond more efficiently to violent and hooligan behaviour of football fans. By connecting theoretical findings and empirical data, the paper examines, within the subject of research in the media context, the examples of fan violence at football stadiums before, during and after football matches. The conclusion is that only with organized social action of all agents, in particular media, a solution to the problem of violence and hooliganism can be reached.
Keywords: media; football; violence; hooligans